2015
DOI: 10.3233/thc-151061
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence detection test by black printed circuit board based microfluidic channel for polymerase chain reaction

Abstract: This paper proposes the optimal structure of a PCB-based micro PCR chip constructed on a PCB substrate using commercial adhesive tapes and plastic covers. The solder mask of the PCB substrate was coated black, and the area where the reaction chamber is attached was legend printed with white silk to minimize the noise during fluorescence detection. The performance of the PCR and fluorescence detection was compared using 6 types of reaction chambers, each made with different double-sided tapes. Three of the cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In a previous study, a micro-PCR chip fabricated with double-sided tape produced results similar to those of conventional PCRs [ 9 ]. It was also confirmed that real-time PCR could be implemented using the micro-PCR chip based on a black PCB, as suggested in previous studies [ 10 , 11 ]. Although the heating pattern circuit, which acts as a heater, is sufficiently wide to involve the microfluidic channel, the DNA amplification is successful.…”
Section: Introductionsupporting
confidence: 84%
“…In a previous study, a micro-PCR chip fabricated with double-sided tape produced results similar to those of conventional PCRs [ 9 ]. It was also confirmed that real-time PCR could be implemented using the micro-PCR chip based on a black PCB, as suggested in previous studies [ 10 , 11 ]. Although the heating pattern circuit, which acts as a heater, is sufficiently wide to involve the microfluidic channel, the DNA amplification is successful.…”
Section: Introductionsupporting
confidence: 84%
“…Because it was difficult to set this resolution with the standard timer provided by MS Windows, we set it to less than 5 ms using a high-precision event timer (HPET). The advantage of this host-local architecture is a reduction in the overall cost [ 29 , 30 , 31 ].…”
Section: The Proposed Smartphone Camera-based Rt-pcr Systemmentioning
confidence: 99%
“…Generally, the PCR step consists of denaturing DNA or RNA at 94 °C–95 °C, annealing the primer at 58 °C–60 °C, and elongating the DNA or RNA using primers at 72 °C–73 °C. The functions related to the execution and file management of the set PCR step file are processed by the host through the file input/output process in the graphical user interface environment [ 29 , 30 , 31 ].…”
Section: The Proposed Smartphone Camera-based Rt-pcr Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time PCR technology enables the real-time monitoring of the amplification process for each cycle with a low contamination rate. The procedure also rapidly produces the analyzed results using the fluorescent detection technique [ 7 , 8 ]. With these advantages, many studies have been conducted on the technique and various real-time PCR devices are available.…”
Section: Introductionmentioning
confidence: 99%